The fusome mediates intercellular endoplasmic reticulum connectivity in Drosophila ovarian cysts. - Snapp, E.L.; Iida, T.; Frescas, D.; Lippincott-Schwartz, J.; Lilly, M.A. (Molecular Biology of the Cell, 2004)
Drosophila ovarian cysts arise through a series of four synchronous incomplete mitotic divisions. After each round of mitosis, a membranous organelle, the fusome, grows along the cleavage furrow and the remnants of the mitotic spindle to connect all cystocytes in a cyst. The fusome is essential for the pattern and synchrony of the mitotic cyst divisions as well as oocyte differentiation. Using live cell imaging, green fluorescent protein-tagged proteins, and photobleaching techniques, we demonstrate that fusomal endomembranes are part of a single continuous endoplasmic reticulum (ER) that is shared by all cystocytes in dividing ovarian cysts. Membrane and lumenal proteins of the common ER freely and rapidly diffuse between cystocytes. The fusomal ER mediates intercellular ER connectivity by linking the cytoplasmic ER membranes of all cystocytes within a cyst. Before entry into meiosis and onset of oocyte differentiation (between region 1 and region 2A), ER continuity between cystocytes is lost. Furthermore, analyses of hts and Dhc64c mutants indicate that intercellular ER continuity within dividing ovarian cysts requires the fusome cytoskeletal component and suggest a possible role for the common ER in synchronizing mitotic cyst divisions.